Prevalence of Sick Building Syndrome among Employees of Shahid Beheshti Hospital in Kashan - Hakime Zamani-Badi; Vali Sarsangi; Mitra Hannani; Hossein Akbari; Ashraf Mazaheri Tehrani (Archives of Occupational Health, 2019)
Background: The sick building syndrome (SBS) is known as an unhealthy condition of occupants of a building, caused by environmental factors such as small space, poor ventilation, and different pollutants in the building. Symptoms of SBS include anxiety, respiratory, dermal, and sensory problems which start by entering a building or slightly after that, and disappear after leaving the building. The aim of this study was to determine the frequency of SBS in the employees of Shahid Beheshti hospital of Kashan. Methods: In a descriptive, cross-sectional study conducted, a sample of 279 randomly-selected employees of Shahid Beheshti hospital in Kashan working during 2016-2017, were involved. The study was performed on four groups of doctors, nurses, servants and employees. To collect the data; a questionnaire was used. It consisted of two parts: demographic data and questions of SBS questionnaire of World Health Organization. The collected data were analyzed using SPSS; and statistical tests such as Chi square and Fisher's exact test were performed and logistic regression were used for multivariate analysis. Results: The prevalence rate of SBS in general, in women and in men was estimated 50.81%, 55.3% and 44.7%, respectively. Symptoms of indisposition (47.3%), skin dryness (41.5%) and headaches (38.9%) had the highest frequency. Studying SBS symptoms in different job groups showed that skin dryness and dry and sore throat in physicians were significantly less than those in the other groups (p<0.05). In logistic regression analysis, the only factor influencing SBS was the staff height (p=0.02). Conclusion: Considering the high prevalence of the symptoms of building syndrome in all of the four groups, paying more attention to improving the working environment, such as the efficiency of the air conditioner system and increasing the entry of fresh air into the departments, increasing the quality of work life would be of utmost importance which would result in motivating and increasing the productivity in the work environment.